Postponement of debt payment obligations through semi-public restructuring - Kurniawan, Itok Dwi; Suwadi, Pujiyono; Santos, Jose Gama; Soehartono (Universitas Ahmad Dahlan, 2025)
Introduction to the Problem: The COVID-19 pandemic has driven many companies in Indonesia to seek Postponement of Debt Payment Obligations (PKPU) and bankruptcy, highlighting the need for more adaptive legal frameworks. Current PKPU mechanisms are viewed as outdated, failing to address conflicts of interest and broader economic impacts. This research proposes a semi-public restructuring model to enhance fairness and inclusivity. Purpose/Study Objectives: This study analyzes the urgency of deconstructing the PKPU framework by introducing semi-public restructuring, which integrates judicial oversight and equitable consideration for all parties involved. Design/Methodology/Approach: This research includes normative legal research. Data analysis uses descriptive methods, deconstruction hermeneutic approaches, cases, legislation, and deduction-syllogism analysis. The legal materials used in this study consist of primary legal sources such as laws and court rulings, as well as secondary materials such as academic literature and legal commentary. Findings: The findings reveal that implementing a semi-public restructuring model in PKPU cases is essential for creating a more balanced and fair resolution process. Unlike current mechanisms that overly favor creditors, this model offers a comprehensive solution by involving the courts in approving restructuring plans, ensuring that all creditors are treated equally. Additionally, the semi-public restructuring model adapts successful principles from other countries, like the UK, to Indonesia’s legal framework. It is important to understand that semi-public restructuring differs from PKPU, which is commonly affirmed in debt restructuring. Semi-public restructuring goes beyond mere debt adjustment, encompassing broader corporate reorganization. This model can provide legal certainty, maintain business continuity, and promote long-term financial stability by considering broader socio-economic impacts. This semi-public restructuring approach aligns with Indonesia’s Pancasila values and has the potential to make the bankruptcy legal system more adaptive and responsive to the nation’s economic challenges. Paper Type: Research Article